Dynamics of Soil Oribatids (Acari) in a Tropical Regeneration Ecosystem of Costa Rica - Rodríguez Arrieta, Jesus Alexander; Retana-Salazar, Axel (ENTOMOTROPICA, 2011)
Population dynamics of four Oribatid mites species are analyzed for further purposes of soil health on three different restoration habitat regime in the Lankester Botanical Garden, Costa Rica. A logarithmic Poisson regression and an alternative Negative Binomial Model were used to estimate statistical interactions between species presence on each habitat. Highest proportions found were constituted by Zetomimus naias and Nothrus willmanni in the latest restored habitat. Besides, a very high proportion of N. willmanni was found in the low disrupted habitat (oldest habitat restored) at the end of the rainy season. This is evidence of successful establishment of N. willmanni in spite of the constantly low organic-matter-recycling-rate, in other words, the low impact on the site. N. willmanni kept high population even when impact had occurred long time ago.